Public Health Nurses and Mothers Challenge and Shift the Meaning of Health Outcomes - Megan Aston; Josephine Etowa; Sheri Price; Adele Vukic; Christine Hart; Emily MacLeod; Patricia Randel (SAGE Publishing, 2016)
Maternal, child, and newborn health is a priority area in Canada and around the world. The work of public health nurses (PHNs) is often invisible and misunderstood. The purpose of this qualitative research project was to explore how universal and targeted home visiting programs for mothers and babies were organized, delivered, and experienced through the everyday practices of PHNs ( n = 16) and mothers ( n = 16) in Nova Scotia, Canada. Feminist poststructuralism and discourse analysis were used to analyze interviews. Concepts of relations of power enabled an understanding of how health outcomes had been socially and institutionally constructed through binary relations. PHNs and mothers spoke about the importance of "softer" health outcomes, including maternal self-confidence and empowerment that had been constructed as less important than health outcomes that were seen to be more tangible and physical. Findings from this research could be used to guide practice and planning of postpartum home visiting programs.